Research Progress of Acupuncture Treatment for Irritable Bowel Syndrome - Zhao, Na; Hui, Jianping; Cao, Ruotong (Journal of Contemporary Medical Practice, 2024)
This article briefly introduces the concept, manifestation, pathogenesis and clinical treatment of Irritable Bowel Syndrome (IBS), and describes the progress of clinical research on the treatment of IBS in recent years from the various aspects of acupuncture therapy, and summarizes the aspects that are still to be perfected in the study of IBS, which is conducive to the further in-depth study and promotion of the treatment of IBS by acupuncture, and improve the therapeutic effect for the benefit of patients. The study summarizes some aspects of the current research on IBS that still need to be improved, which is conducive to the further in-depth research and promotion of acupuncture for IBS, improving the therapeutic effect and benefiting patients.